2013
DOI: 10.1111/den.12042
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a simple predictive scoring system for pancreatic fistula after laparoscopy‐assisted gastrectomy

Abstract: This study demonstrated that POPF after LAG is associated with specific preoperative and postoperative factors. With a simple predictive scoring system, patients at high risk for POPF can be accurately identified. This simple predictive scoring system will be useful for many clinicians to assess the risk of POPF after LAG and start treating at-risk patients earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The incidence of POPF after LG is reported to be 1.7 to 7.2% [ 4 , 7 , 11 , 25 , 26 ], and it was reported to be higher compared with after OG [ 7 , 13 15 ]. POPF is thought to be caused by several factors, including direct damage to the pancreas or lateral thermal injuries by surgical instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of POPF after LG is reported to be 1.7 to 7.2% [ 4 , 7 , 11 , 25 , 26 ], and it was reported to be higher compared with after OG [ 7 , 13 15 ]. POPF is thought to be caused by several factors, including direct damage to the pancreas or lateral thermal injuries by surgical instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers used the drained body fluid amylase concentration [8, 11] or C‐reactive protein concentration [8, 10]. One study used a predictive scoring system with risk factors such as age, drained amylase concentration, body mass index, and other parameters [7, 8, 10]. Although early findings of abnormalities and a quick response would lead to the prevention of severe POPF, the postoperative period might already be too late for effective therapy, or the drain might not be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have come up with different markers and models like DPA, PPA, CRP, WBC and many other indicators for the prediction. 1 , 5 7 , 17 , 31 33 Molinari et al 21 concluded that DPA1 > 5000 U/L was a significant predictive factor for POPF with a sensitivity and specificity of 93 and 84%, respectively. Sutcliffe et al 17 reported that using 350 U/L as a cutoff, low DPA1 excluded POPF with sensitivity, specificity, positive predictive value, and negative predictive value of 100, 79, 41 and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%